PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN MENGGUNAKAN JASA SABLON RAINBOW CREATIVE SANGATTA - Silvani Hapsari; Simunawir Sitoro; Jumri Jumri (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2026)
This research aims to analyze the influence brand image and price on the decision to use screen printing services Rainbow Creative Sangatta. The research method used is a quantitative method with the analytical method used in this research being the multiple linear regression analysis method and hypothesis analysis with the SPSS 25 application. The sample in this research consisted of 66 respondents. The independent variable is a variable brand image and price and the dependent variable, namely the decision to use services. The research results show that variables brand image (X1) partially has a positive and significant influence on the decision to use services (Y) with a t valueheatingg 4,503 > ttable 1.669, and the price variable (X2) has a positive and significant influence on the decision to use services (Y) with a t valueheatingg 3,296 > ttable 1,669. Based on simultaneous testing of variables brand image and price also has a positive and significant influence on the decision to use services with a Sig value < 0.05 (0.000 < 0.05), and the coefficient of determination (R) value obtained in this study is 0.600. This means that 60% of the decision variables to use services can be explained by variables brand image (X1) and price (X2). Meanwhile, the remaining 40% can be explained by other independent variables that were not included in this research.